Development of GIS-Based Pangasius Aquaculture Areas Using Analytical Hierarchy Process (AHP) in Tulungagung Regency, East Java, Indonesia - Nurhabib, Asro; Sartimbul, Aida; Primyastanto, Mimit; Sriwidodo, Maheno; Handoko, Lugu Tri Handoko; Rahayu, Andra Rejekineng; Pardiansyah, Dedi; Utami, Risnita Tri (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract   Highlight Research The author mentioned four highlights from their research: 1. GIS and AHP were integrated to assess land suitability for Pangasius aquaculture in Tulungagung Regency. 2. 59% of the region (976,885.71 ha) was identified as suitable or highly suitable for aquaculture expansion. 3. Water quality, soil conditions, and infrastructure were key factors influencing aquaculture feasibility. 4. Sustainable planning is needed to balance aquaculture expansion with existing land uses like agriculture and settlements. 5. The GIS-based model serves as a policy tool for efficient and sustainable Pangasius aquaculture development.     Abstract Tulungagung Regency in East Java Province has an export demand of 300,000-400,000 tons per year. The high demand for exports spurred the people and government of Tulungagung Regency to develop pangasius aquaculture areas. This will have a negative impact if carried out without a land suitability assessment. The study aimed to analyze the parameters of pangasius aquaculture and map the potential areas for pangasius aquaculture using AHP and GIS-based analysis. This research was conducted from January to August 2022 in Tulungagung Regency, Indonesia. Several stages were carried out, including primary data collection (water quality, soil quality, and infrastructure), secondary data collection (literature, reports, fisheries statistics data, government statistical data, and journals/articles), application of land suitability assessment, and pangasius farming area suitability analysis. Land suitability analysis consists of measuring water quality parameters (DO, temperature, TDS, pH, ammonia, and nitrate), soil quality (texture, pH, and slope), and infrastructure (roads, markets, hatcheries, and fillet factories) using the Analytical Hierarchy Process method (AHP), which includes standardization, determination of weights, and combining the weights of land suitability maps, which are then mapped by ArcGIS Software. Most of the land conditions for the pangasius aquaculture areas in Tulungagung Regency are moderately suitable, suitable, and most suitable, with percentages of 30, 21, and 28%. The area that can be developed for pangasius aquaculture is 976885.71 ha, with the most suitable category being 2619.35 ha, the appropriate category being 2235.74 ha, and the most suitable category being 4913.77 ha.